WLAN IEEE 802.11b performance measurement and handover mechanism / Abdulmukti Ahmad - Ahmad, Abdulmukti (2007)
The project is focused on measurement analyze of the IEEE 802.11b WLAN performance. A survey of the parameters that affect its performance and an experimental investigation of this impact have been performed as a first step measurements are conducted using the distance method between mobile and Access Point to measure the signal strength. The result of this signal strength is used in the mathematical calculation in order to develop the mathematical model for indoor signal strength. The thesis will go through a rigorous mathematical analysis. First we use an analytical model to verify our measurements results. In the new era of wireless communication, Wireless Local Area Network (WLAN) has emerged as one of the key players in the wireless communication family. There are many obstacles when deploying WLAN, which demands seamless indoor handover. The access point should have the appropriate coverage suitable to the propagation characteristic of the building. The wireless network planner needs a comprehensive tool to implement efficient WLAN network. In this thesis, we have developed a mathematical path loss model using OPNET 10 simulation design tool. By using this simulation program, WLAN planner will be able to setup the access point for the optimum propagation coverage. WLAN products may exhibit the limitation in coverage when performing in crowded office or building due to the propagation loss, transmits power, receive power, fading and other basic obstacles. If user needs a higher data rate for the WLAN, the burden to create seamless coverage becomes crucial. The Network designers need a comprehensive method to locate the Access Point (AP) at the correct angle of the building. If more APs have been deployed, it may increase the cost unnecessarily, however with less APs may compromise the coverage area. In other words the network planner needs to have a first hand experience with the Radio Frequency (RF) characteristic of the facilities. This thesis attempts to provide an efficient method to measure the propagation characteristic for indoor environment using the OPNET 10 simulation software. For the indoor environment, there are two types of elements; namely static and dynamic elements.